The suppression of cultural memory and identity in Bosnia and Herzegovina - Pettigrew, David (Multidisciplinary Perspectives on Genocide and Memory, 2018)
This chapter identifies an orchestrated effort in “Republika Srpska”—an entity within Bosnia and Herzegovina that was recognized by the 1995 Dayton Peace Agreement − that is designed to prevent survivors of the genocide from erecting memorials to the victims in such locations as Višegrad, Prijedor, and Foča. While memorials for victims have been prohibited, and survivors have been prevented from using the term “genocide,” memorials to the perpetrators have been installed in the center of Višegrad, and near the Trnopolje concentration camp in Prijedor Municipality. In the hills above Sarajevo, in a location from which the city’s residents were attacked during the siege, a plaque honoring indicted war criminal Ratko Mladić has been installed. Accordingly, this chapter considers the extent to which the discriminatory practices regarding memorials in Republika Srpska constitute a violation of human rights. Further, the chapter argues that, following Raphael Lemkin’s definition of genocide, the prohibitive policies in Republika Srpska with respect to memorials and commemorative practices constitute nothing less than a continuation of the genocide, a second phase of the genocide designed to ensure the permanent erasure of a world that was destroyed. These human rights violations and the continuation of the genocide are a troubling testament to the failure of the international community in Bosnia, and to the problematic legacy of the Dayton Peace Agreement.
Keywords: Apartheid; Cultural memory; Dayton Peace Agreement; Dayton peace agreement; Health Psychology; Health psychology; History of World War II and the Holocaust; Human rights; Prohibited memorials; Public Health; Public health; Raphael Lemkin; Sociology; Sociology, general; World War, 1939-1945; dept.phi